SOREN KIERKEGAARD'S EXISTENTIALISM: A STUDY ON HOW TO ENJOY LIFE DURING THE POST-TRUTH ERA - Saputra, Riki; Ritonga, Mahyudin; Arrasyid (UIN Raden Mas Said Surakarta, 2024)
This study aims to explain the means of deriving enjoyment in life during the post-Truth era by drawing upon the existentialist values of Soren Kierkegaard. A qualitative approach is adopted with a conceptual design, utilizing exploratory, interpretative, and analytical methods. The results showed that individuals were able to derive enjoyment from life during the Post-Truth Era by embracing the following Soren Kierkegaard's existentialism values: Firstly, being oneself; living under the narrative of the heart and mind. Secondly, being moral and adhering to universal rules. Thirdly, living a religious life, having a direct connection with God, and being critical of religion. Previous studies had extensively explored Soren Kierkegaard's existentialism, but none specifically examined its concept as a means of enjoying life.